Phonetics before speech - Mildner, Vesna (2009)
The study analyses speech perception and speech production in children with cochlear implants on the basis of some earlier research. In speech perception part, perception of vowels and consonants was observed. Special attention was paid to voicing, and place and manner of articulation in consonants. The results showed greater confusion between closer vowels than between distant ones. In consonants, voicing was showen to be the most difficult and the manner the easiest feature to perceive. Affricate and fricatives were more difficult to perceive than stops. Children with CI performed better than children with HA. In production part, F1 and F2 were observed in vowels, duration accuracy, stop-fricative pattern of affricates /c/ and /č/ and noise frequency in fricatives /s/ and /š/. The results showed that vowel space was organized like vowel space of hearing controls with possibly some residual fronting, that affricates were shorter and produced with increasing accuracy and that fricatives were better separated in terms of noise frequency. Some of the general conclusions are: continuous therapy is of utmost importance, more time should be spent on more problematic sounds, progression is non-linear and production mirrors perception.